2017
DOI: 10.1093/ijnp/pyx017
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Oxidative Stress Relieves Stress-Induced Behavioral and Cognitive Impairments in Rats

Abstract: Background:Persistent psychological stress often leads to anxiety disorders and depression. Benzodiazepines and selective serotonin reuptake inhibitors are popular treatment options but have limited efficacy, supporting the need for alternative treatment. Based on our recent preclinical work suggesting a causal link between neurobehavioral deficits and elevated oxidative stress, we hypothesized that interventions that mitigate oxidative stress can attenuate/overcome neurobehavioral deficits.Methods:Here, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…There is some evidence that cortisol, released by stress, increases the production of oxidative species (Aschbacher et al, 2013;S ims ek, Yüksel, Kaplan, Uysal, & Aktas , 2016). Basic science research in animal models of social stress confirms that aversive social contexts induce oxidative stress (Schiavone et al, 2013;Solanki et al, 2017). The cross-sectional design of this study does not permit causal inferences to be made regarding increased oxidative stress and borderline and narcissistic personality disorders.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There is some evidence that cortisol, released by stress, increases the production of oxidative species (Aschbacher et al, 2013;S ims ek, Yüksel, Kaplan, Uysal, & Aktas , 2016). Basic science research in animal models of social stress confirms that aversive social contexts induce oxidative stress (Schiavone et al, 2013;Solanki et al, 2017). The cross-sectional design of this study does not permit causal inferences to be made regarding increased oxidative stress and borderline and narcissistic personality disorders.…”
Section: Discussionmentioning
confidence: 80%
“…Although interconnected with what is generally considered to be the stress response system centered on the hypothalamic-pituitary-adrenal axis, oxidative stress is a largely cellular process (Schiavone, Jaquet, Trabace, & Krause, 2013). Social stressors relevant to personality disorder, such as maternal deprivation, social defeat, and social deprivation, have been found to increase oxidative stress (Markovic et al, 2017;Schiavone et al, 2009;Solanki, Salvi, Patki, & Salim, 2017). We have previously found that impulsive aggression and the presence of personality disorder are both associated with increased oxidative stress, as evidenced by elevated blood levels of 8-hydroxy-2'-deoxyguanosine (8-OH-DG; Coccaro, Lee, & Gozal, 2016).…”
mentioning
confidence: 99%
“…All these compounds increase primarily the cytosolic Ca 2+ concentration, followed by mitochondrial ROS formation and eventually followed by apoptosis and cell death. But also psychosocial stress results in the increase of cytosolic Ca 2+ concentration, as shown in isolated cardiomyocytes [85], in platelets [86], hippocampal-derived HT22 cells [87], urothelial cells [88], and cardiomyocytes [89]. The neurotoxic effect of glutamate in neurons via the N-methyl-D-aspartat-receptor was related to an increase of cytosolic Ca 2+ and the formation of ROS [90,91].…”
Section: Stress and Calcium Signalingmentioning
confidence: 97%
“…Notably, DHCA was also found to have strong inhibitory properties on other key inflammatory cytokines such as IL1β and IL-12. One of the best-studied polyphenols, resveratrol, has both antidepressants effects in the social defeat stress model ( Finnell et al, 2017 ; Renthal et al, 2009 ) and pro-cognitive effects in models of stress-related cognitive impairments ( Solanki et al, 2017 ). In part, the pro-resilient effects of resveratrol are thought to be mediated by up-regulation of a sirtuin 1 (SIRT1)-dependent pathway ( Kim et al, 2016 ) that can epigenetically reprogram oxidative stress and pro-inflammatory gene expression profiles ( Strycharz et al, 2017 ).…”
Section: Immune Influences On Resiliencementioning
confidence: 99%